The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1039/b913746g
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-ionic liquid gels for enhanced gas transport

Abstract: Remarkably increased permeabilities for the separation of an important binary gas pair (CO2/N2) by polymer-ionic liquid gel membranes are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 19 publications
2
58
0
Order By: Relevance
“…For example, it was demonstrated that using nanofiltration membranes as support materials sufficient capillary binding forces can be provided that help the ionic liquid to stay in the pores even at higher pressure [32,39]. The stability and probably the pressure resistance of the SILMs can also be improved by coating the ionic liquids with a dense polymer (e.g.…”
Section: 2mentioning
confidence: 99%
“…For example, it was demonstrated that using nanofiltration membranes as support materials sufficient capillary binding forces can be provided that help the ionic liquid to stay in the pores even at higher pressure [32,39]. The stability and probably the pressure resistance of the SILMs can also be improved by coating the ionic liquids with a dense polymer (e.g.…”
Section: 2mentioning
confidence: 99%
“…Hong et al [25] reported a series of PVDF/[emim][BF 4 ] polymer gels that exhibited impressive gas separation performance. The best performance of their polymer gels had CO 2 permeability and CO 2 /N 2 selectivity of 400 Barrer and 60, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement of ionic liquids from the support can still happen with sufficient trans-membrane pressure difference. To address this problem, efforts have been made to develop a solid-state material that can combine the liquid-like permeability of ILs with a solidlike structure, using either low-molecular weight gelators [56], or compatible macromolecules, such as chemically-crosslinked polymerized ionic liquids (PIL) [57][58][59][60][61][62]. These IL-based composite materials have shown improved mechanical stability and good separation performance.…”
Section: Introductionmentioning
confidence: 99%